SOME ASPECTS OF BREEDING WITH POLEMONIUM CAERULEUM L. - Firdaus M. Hazieva; Irina N. Korotkikh; Irina V. Basalaeva; Tat'yana Е. Samatadze (Siberian Journal of Life Sciences and Agriculture)
Background. Methods of artificial polyploidization are not used enough in medicinal crop production. The use of colchicine causes obvious morphological changes in the obtained P. caeruleum polyploids and changes in the productivity of raw materials and seeds. The research was conducted at the All-Russian Scientific Research Institute of Medicinal Plants, Moscow region.